Energy management for the smart home - Sikasote, Nataizya (Department of Electrical Engineering, 2018)
Utility providers are under constant pressure to meet the ever-increasing demand for energy with a finite production capacity. Due to this, utility providers need to ensure that the demand does not exceed the supply. The use of demand response programs has been used as a solution to better match the available supply to the demand experienced on the grid. While demand response programs may improve the relationship between the supply and the demand, increasing consumer participation can further improve the effectiveness of demand response programs. The level of consumer participation is highly dependent on the incentives offered and the convenience of participating in the demand response program. However, most of these programs require consumers to actively monitor the available services and take appropriate action on their appliances. Home energy management systems attempt to provide convenience to consumers as well as increase their participation in demand response programs. They do this by enabling autonomous control and remote control of appliances. In addition, a home gateway makes it possible for the consumer and utility provider to interact with devices in the home remotely. Current solutions host the home energy management software on a home gateway or on a dedicated device in the home. Furthermore, these systems make use of proprietary software and devices to monitor and control the home environment. However, proprietary systems are costly to implement and maintain due to their dependence on the developers and the varying needs of consumers. This dissertation proposes a home energy management system solution that makes use of a standardized distributed machine-to-machine (M2M) middleware framework to support heterogeneous devices, technologies and protocols. In addition, the proposed solution shifts the software logic of the home energy management system from the gateway to a private cloud. This allows the system to leverage the benefits of virtualization and cloud computing such as cost efficiency, faster deployment and easier maintenance of the system. The proposed solution was implemented using a European Telecommunications Standards Institute (ETSI) compliant distributed M2M middleware framework (i.e. OpenMTC) and an open-source private cloud platform (i.e. OpenStack). A prototype was developed and tested with demand response programs that included a control demand response (DR) service, a consumption monitoring service and a time-of-use (ToU) service. In addition, the prototype made use of various third party applications, protocols and devices to support the aforementioned demand response services and provide automated and remote control of home appliances. Finally, an evaluation of the proposed system was conducted and concluded that the number of home energy management systems subscribed to the defined services influenced the effectiveness of these services because of the additional processing that the utility provider is required to perform.